Power allocation in wireless network virtualization based on resource sharing - Bin CAO; Wen-qiang LANG; Zhuo CHEN; Yun LI (Tongxin xuebao)
In traditional wireless network, resource couldn’t be efficiently and flexibly. To this end, wireless network virtualization was used to manage and share resource. A game theory based two steps power allocation scheme for wireless network virtualization, called G2SPA, was proposed, which designed a stackelberg equilibrium (SE)price strategy based on the interactions between SP and mobile user equipme (MUE), and then MacAfee based auction to reallocate leisure resource was performed. The numerous experimental simulation results show that the rightness and effectiveness of G2SPA.